ANXIETY EFFECT ON STUDENTS AND PERFORMANCE IN BIOLOGY: A CASE STUDY AMONG SECONDARY SCHOOLS IN SOKOTO CITY, NIGERIA - Miya, Yusuf Yahaya; Dambam, Sa’eed Abdullahi; Abdulkareem, Jamil Hassan; Sarkingobir, Yusuf; Yabo, Aminu M. (Sanata Dharma University Yogyakarta, 2023)
The Sokoto state needs biology-based students for the making of many useful professionals that works in a diverse array of human lives. However, there is a report showing poor performance in the subject. Anxiety is an issue that may affect education; thus, this work aimed to assess the issue of anxiety among students of biology in secondary school, the related causes, and control. The study design applied was a survey (questionnaire) among 400 students in Sokoto and the data was managed using descriptive statistics. Sources revealed include: How often do you hear from your family while on campus had the greatest percentage with 40.0%, then by Lack taking in a well-balanced diet with 30.0 %, How often have you been following your time table had 20.0%, followed by Distractions or disturbances from a roommate on campus (7.5%), and the least was How often have you been angered because of things that were beyond your control on campus with 2.5%. The effects of anxiety on academics include: Anxiety distracting from the lesson (40.0%), and reduces morale in academics (30.0%). Anxiety prevents students from finishing their assignments (20.0%), and elicits absenteeism (10.0%). Anxiety management includes: Major ploy is enough time and participating in extracurricular activities. Guidance and counselling/discussions with friends are helpful. Thus, academic anxiety can be tamed for better learning. Education on anxiety, enough rest, staying focused, and exercise are needed to enhance students’ academic performance.